Saints and City Models: Contested Borders and the Representation of Subject Towns Between Florence and Siena - Strauss, Scarlett H. (Artium Quaestiones, 2024)
The Black Death in 1348 was followed by a period of ongoing skirmishes between the city-states of Florence and Siena, marked by active territorial expansion, mercenary raids, and larger wars. Subject towns were profoundly affected by this turmoil and came under the alternating influence and control of the two dominant cities. In the face of this unrest, one way for inhabitants of subject towns – including Lucignano, San Gimignano, Montepulciano, and Cortona – to manifest both local identity and political allegiance was to commission artworks. Of the paintings made for these contested sites from the late fourteenth to the early sixteenth centuries, a number include depictions of the town for which the image was made, held by a patron saint. These city models offer a valuable lens on a marginalized area, providing insight into how subject towns were conceptualized and understood by patrons, artists, and viewers. Saintly advocacy and protection are frequently invoked in relation to recent or ongoing political upheaval, emphasizing civic and sacred loyalties or affiliations. The depiction of towns as models held by saints also echoes the actual transactional changes of ownership that frequently occurred, reflecting the multifaceted power dynamics between artist and patron, or between dominant city and subject town. Furthermore, the prevalence of such city models in paintings commissioned from Sienese artists suggests a particular Sienese “border mentality,” or an awareness of the intersections of identity that result from existing on shifting cultural and political borders.